EXPLORING THE ROLE OF COMPUTER SELF-EFFICACY ON POST-GRADUATE STUDENTS RESEARCH ORIENTATION (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
Technology advancements have transformed how students engage with academic content and conduct research. As post-graduate students navigate the complexities of their research journey, their self-efficacy beliefs regarding computer skills play a pivotal role. This research paper investigates the relationship between computer self-efficacy and research engagement among post-graduate students. Ninety-six students enrolled in graduate programs in public universities in the River States of Nigeria participated in the study. Data were collected using self-report measures. The result supports the hypothesis that the main independent variables of the study statistically significantly predicted research orientation, F (1, 94) = 31.205, p < 0.05. All two variables contributed significantly to the prediction, p < .05. The result revealed that the predictor variable contributed 12.2% of the variance in the post-graduate research orientation. The result has implications for research development in academia.